Factors associated with low consumption of fruits and vegetables by preschoolers of low socio‐economic level - Julia L. Valmórbida; Márcia R. Vitolo (Brazilian Society of Pediatrics, 2014)
Objective: To evaluate factors associated with low consumption of fruits and vegetables among preschoolers from families treated at basic health centers in Porto Alegre, RS, Brazil. Methods: This was a cohort study nested in a randomized field trial. Data collection was performed through structured questionnaires to obtain demographic and dietary data, combined with two 24‐hour recalls in the age groups 12-16 months and again at 2-3 years of age. Data on the consumption of one daily serving of fruits (80 g) and vegetables (60 g) were evaluated, as well as consumption of non‐recommended foods such as candy, chocolate, and soft drinks. Statistical analyses were performed using Poisson regression with robust estimation. Results: A total of 388 children aged 2‐3 years were evaluated; of these, 58% and 87.4% did not consume one daily serving of fruits and vegetables, respectively. The following factors were negatively associated with fruit consumption: family income higher than four minimum wages, (p = 0.024), lower paternal educational level (p = 0.03), and lower fruit consumption at 12-16 months (p = 0.002). Factors negatively associated with the consumption of vegetables were low paternal educational level (p = 0.033) and consumption of high‐sugar content beverages at 12-16 months (p = 0.014). Conclusion: This study demonstrated a high prevalence of children who consumed less than one daily serving of fruit and vegetables; early feeding practices, parental education, and family income were associated with this process.